Pengaruh Peran Pengendalian Internal, Kesesuaian Kompensasi, Dan Budaya Etis Organisasi Terhadap Pencegahan Fraud Tenaga Penagih Di PD Pasar Surya Di Kota Surabaya - Endrianto Sahedtyo Nugroho Suhadak; Iwang Suwangsih; Ketut Witara (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Fraud is a risk that is prone to occur in organizations engaged in direct financial transaction activities, including regional government-owned enterprises. PD Pasar Surya Surabaya has the potential for fraudulent practices, particularly among market levy collectors, thus requiring effective preventive measures. This study aims to analyze the effect of internal control, compensation suitability, and organizational ethical culture on fraud prevention, both partially and simultaneously. The research employs a quantitative approach with a causal associative method. The population consists of all active levy collectors of PD Pasar Surya Surabaya, totaling 40 individuals, using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The results indicate that internal control, compensation suitability, and organizational ethical culture have a significant effect on fraud prevention, both individually and collectively. These findings emphasize the importance of implementing effective internal control systems, providing fair compensation, and strengthening organizational ethical values to minimize the risk of fraud